Antibacterial Layer-by-Layer coatings for medical implants - Escobar, Ane (2021)
The widespread occurrence of nosocomial infections and the emergence of new bacterial strands calls for the development of antibacterial coatings with localized antibacterial action that are capable of facing the challenges posed by increasing bacterial resistance to antibiotics. The Layer-by-Layer (LbL) technique, based on the alternating assembly of oppositely charged polyelectrolytes, can be applied for the non-covalent modification of multiple substrates, including medical implants. Polyelectrolyte multilayers fabricated by the LbL technique have been extensively researched for the development of antibacterial coatings as they can be loaded with antibiotics, antibacterial peptides, nanoparticles with bactericide action, in addition to being capable of restricting adhesion of bacteria to surfaces. In this review, the different approaches that apply LbL for antibacterial coatings, emphasizing those that can be applied for implant modification are presented.